2000
DOI: 10.1080/02640410050082305
|View full text |Cite
|
Sign up to set email alerts
|

Retroactive interference effects of mentally imagined movement speed

Abstract: In two retroactive interference experiments, we assessed the eþ ect of mentally imagined movement speed on subsequent motor performance. All participants performed a sequential motor action at three speeds during a baseline test and a retention test. During the retention interval of Experiment 1, the participants (n = 50) physically performed the action at a slow speed, physically performed it at a fast speed, imagined it at a slow speed, imagined it at a fast speed, or performed a no-practice control task. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 24 publications
2
31
2
2
Order By: Relevance
“…Previous research has suggested that mental practice of a motor skill can cause interference for subsequent motor performance (e.g., Gabriele, et al, 1989;Hall, et al, 1995;Boschker, et al, 2000;Wohldmann, et al, 2008). The current study's findings are consistent with this.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has suggested that mental practice of a motor skill can cause interference for subsequent motor performance (e.g., Gabriele, et al, 1989;Hall, et al, 1995;Boschker, et al, 2000;Wohldmann, et al, 2008). The current study's findings are consistent with this.…”
Section: Discussionsupporting
confidence: 92%
“…MI research has received strong theoretical and empirical support for temporal equivalence, and there is now ample evidence that the time course of mentally simulated actions should ideally be correlated with the time taken to perform the same movement (e.g., Decety, Jeannerod, & Prablanc, 1989;Holmes & Collins, 2001;Papaxanthis, Pozzo, Skoura, & Schieppati, 2002; for reviews, see Malouin et al, 2008). Previous data also provided evidence that performing MI intentionally at a faster/slower pace resulted in altering subsequent actual times (Boschker, Bakker, & Rietberg, 2000;Louis et al, 2008), highlighting the necessity to control imagined times to avoid using MI inappropriately. Therefore, the present findings extend our understanding of the specific guidelines for implementation of MI practice by suggesting that relaxation might negatively affect MI times.…”
Section: Discussionmentioning
confidence: 92%
“…Second, although athletes did report using all three image speeds, at present, adequate research has yet to be conducted examining the effectiveness of employing slow-and fast-motion images. Although beyond the scope of the current study, a few studies examining the effect of fast-and slow-motion image speed use have been conducted (e.g., Andre & Means, 1986;Boschker, Bakker, & Reitberg, 2000). Recently, O & Munroe-Chandler (2008) have noted that these studies may have been limited by certain methodological and statistical issues.…”
Section: Discussionmentioning
confidence: 91%